Fabrication of periodically poled lithium niobate waveguides for broadband nonlinear photonics - Furkan Ayhan; Markus Ludwig; Tobias Herr; Victor Brasch; Luis Guillermo Villanueva (APL Photonics)
Nonlinear optics is the precursor for many of the modern-day applications of photonics, including femtosecond pulse synthesis, precision spectroscopy, and metrology. In the last decade, nanophotonic waveguides have not only boosted the efficiencies of nonlinear effects but also unlocked new degrees of freedom in the design process and enabled the monolithic integration of multiple nonlinear devices. Now, the advent of thin-film variants of platforms with a strong second-order nonlinearity such as lithium niobate-on-insulator (LNOI) enables entirely new applications while further improving efficiency for the existing ones. However, suitable fabrication processes are needed to exploit the full potential of these new platforms. Here, we introduce a process for fabricating high-confinement lithium niobate waveguides with periodic poling. Our waveguide designs enable both third-order nonlinear χ(3) broadening and sum frequency generation (SFG) up to the fourth harmonic through a quasi-phase-matched χ(2) section. In supercontinuum (SC) experiments, our devices produce multi-octave SC spectra when pumped with an 80 fs mode-locked laser at 1560 nm.